Small and large PROS1 deletions but no other types of rearrangements detected in patients with protein S deficiency - Lind-Halldén, Christina; Dahlén, Anna; Hillarp, Andreas; Zöller, Bengt; Dahlbäck, Björn; Halldén, Christer (Thrombosis and Haemostasis, 2012)
Protein S deficiency is a dominantly inherited disorder that results from mutations in the PROS1 gene. Previous sequencing of the gene failed to detect mutations in eight out of 18 investigated Swedish families, whereas segregation analyses detected large deletions in three out of the eight families. The present study investigates more thoroughly for the presence of deletions but also for other types of rearrangements. FISH analysis confirmed the existence of the three previously identified large deletions, but failed to identify any other type of rearrangement among the eight analysed families. MLPA analysis of the PROS1 gene revealed two smaller deletions covering two and four exons, respectively. Thus, deletions could be found in five out of eight families where no point mutations could be found despite sequencing of the gene. Twelve additional, not previously analysed, families were subsequently analysed using MLPA. The analysis identified two smaller deletions (3 and 4 exons). Including all PS-deficient families, i.e. also the 10 families where sequencing found a causative point mutation, deletions were identified in seven out of 30 PS-deficient families. A strategy of sequencing followed by MLPA analysis in mutation-negative families identified the causative mutation in 15 out of 18 of Swedish PS-deficient families. Most deletions were different as determined by their sizes, locations and flanking haplotypes. FISH (8 families) and MLPA analysis (20 families) failed to identify other types of rearrangements.
Keywords: Protein C/S pathway; molecular biology methods; familial thrombosis; venous thrombosis; thrombophilia